2007
DOI: 10.1007/s11783-007-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Pollution of NPEOs in four municipal sewage treatment plants in the north of China

Abstract: The concentration and distribution of nonylphenol polyethoxylates (NPEOs represents the mixture, and NPnEO represents the monomer) and its metabolites in the influent and effluent of four municipal sewage treatment plants (STPs) in the north of China were measured. Moreover, the concentration and distribution of the above chemicals in the sludge of two STPs were also determined, and the transfer and fate of NPEOs in the sewage treatment process were discussed primarily by analyzing the distribution of the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(26 reference statements)
2
5
1
Order By: Relevance
“…It is clear that the total concentrations of nonylphenolic compounds (NP-c) in the dry weather is related to industrial and domestic wastewater content in the WWTPs influents, i. e., 0.115 to 0.183 μmol/L of NP-c in the WWTPs receiving both industrial and domestic wastewaters, and 0.347 μmol/L of NP-c in the WWTP receiving only domestic wastewater. The concentrations of nonylphenolic compounds detected in this study fell into the range reported in other literatures (Ma et al, 2002;Planas et al, 2002;Hou and Sun, 2006;Stasinakis et al, 2008), but were at low level compared to those observed in the European countries, such as Switzerland (2.42-4.05 μmol/L) (Ahel et al, 1994) and United States (425-894 μg/L for NP0-16EO) (Loyo-Rosales et al, 2007), indicating that the contamination in Beijing seemed less heavy than abroad, probably due to less consumption of NPnEOs surfactants in Beijing.…”
Section: Npneos and Their Metabolites In The Influents And Effluents supporting
confidence: 85%
“…It is clear that the total concentrations of nonylphenolic compounds (NP-c) in the dry weather is related to industrial and domestic wastewater content in the WWTPs influents, i. e., 0.115 to 0.183 μmol/L of NP-c in the WWTPs receiving both industrial and domestic wastewaters, and 0.347 μmol/L of NP-c in the WWTP receiving only domestic wastewater. The concentrations of nonylphenolic compounds detected in this study fell into the range reported in other literatures (Ma et al, 2002;Planas et al, 2002;Hou and Sun, 2006;Stasinakis et al, 2008), but were at low level compared to those observed in the European countries, such as Switzerland (2.42-4.05 μmol/L) (Ahel et al, 1994) and United States (425-894 μg/L for NP0-16EO) (Loyo-Rosales et al, 2007), indicating that the contamination in Beijing seemed less heavy than abroad, probably due to less consumption of NPnEOs surfactants in Beijing.…”
Section: Npneos and Their Metabolites In The Influents And Effluents supporting
confidence: 85%
“….095 μmol/L for NP and 0.116~0.365 μmol/L for NPEOs (Hao et al 2007;Hou and Sun 2006;Lian et al 2009). Average concentrations of NP and NPEOs of these four major STPs were used to calculate their PCCs by equation (1) according to an investigation of the influent volume and population served of the STPs in the Wenyu River catchment (shown in the Table S2 in supporting information).…”
Section: Simulation Scenario Buildingmentioning
confidence: 99%
“…NP, NP 1 EO, and NP 2 EO were frequently detected in water, sediment, and sewage sludge at high concentrations (Hou and Sun 2006;Ghanem et al 2007;González et al 2010). However, the occurrence of NP and NP 1 EO in soil has not been as well documented as has their occurrence in the aquatic environment (Soares et al 2008).…”
Section: The Occurrence Of Np and Np 1 Eo In Vegetable Soil In Donggumentioning
confidence: 99%
“…Many studies have been conducted to investigate the occurrence of NP and NPEOs in different environmental matrices (Ying et al 2002;Hou and Sun 2006;Ghanem et al 2007;Soares et al 2008;González et al 2010). NP is detected frequently in various matrices, such as sewage sludge, effluents from sewage treatment plants, river water and sediments, and groundwater and has a wide range of concentrations of up to several thousand lg L -1 in surface waters and up to several hundred mg kg -1 in sediment samples (Ying et al 2002;Soares et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation